Productive performance and adaptation of Jatropha curcas L. in three ecoregions in Colombia - Campuzano-Duque, Luis Fernando (2020)
Introduction. Jatropha curcas L., is a species with high oil content suitable for biofuel; however, due to its wild condition, the yield of fruit and oil is low; therefore, it warrants genetic improvement. Objective. To know the productive performance of J. curcas in three ecoregions of Colombia. Materials and methods. The work was carried out from 2012 to 2014. A randomized complete block design with fifteen genotypes in three ecoregions (dry Caribbean, Inter-Andean Valley and Orinoquia) was established. The AMMI model and its biplot graph were used to determine phenotypic stability of the fruit yield and with the oil yield the net benefit and the benefit-cost ratio were determined. Results. In two of the three ecoregions used; dry Caribbean and Inter-Andean Valley, J. curcas presented an accumulated fruit yield of 3.6 t ha-1 and 6.7 t ha-1, respectively; in the Orinoquia region the yield was less than 0.1 t ha-1. The cost of a liter of J. curcas oil was US$1.07 for Albania (dry Caribbean) and US$1.24 for Espinal (Inter-Andean Valley), higher than that of African palm oil (Elaeis guineensis) of US$0.89. Conclusion. The fifteen J. curcas genotypes used in this study showed the best productive performance in Albania (dry Caribbean) and Espinal (Inter-Andean Valley), and the CJC3 genotype was the one with the best fruits and oil production.